Standardization of Technology and Quality Evaluation of Chicken Meat en Meat Biscuits Biscuits - Jaiswal, Raj Kumar; Pathak, V.; Singh, V.P.; Goswami , M. (Journal of Meat Science, 2019)
The chicken meat biscuits were developed using refined wheat flour and various levels of meat (0, 40, 50 and 60 percent). Chicken meat biscuits prepared by replacement of refined flour with three different meat levels were of acceptable quality. On the basis of study it was concluded that product C (50% chicken meat powder) and product D (60% chicken meat powder) showed higher sensory scores and nutritional value, but mean TBA, FFA, aw, TPC etc values were reported to be higher in D as compared to C due to higher amount of moisture and higher fat percentage in D. The overall mean values showed decreasing trend for moisture, emulsion stability, cooking yield, texture profile values etc with enhancement in the level of meat. The reverse trend was also observed in the values of fat, protein, ash and water activity.